Eco-friendly decolorization of synthetic dyes using radiation-induced whole cell biocatalyst with enhanced copper resistance - Jeon, Min Seo; Jeong, Soyoung; Yang, Seul-Ki; Jung, Kwang-Woo; Gong, Gyeongtaek; Ahn, Jung Ho; Seo, Myung-Ji; Lim, Sangyong; Jung, Jong-Hyun (Academic Press, 2025)
Toxic and carcinogenic compounds, such as synthetic dyes and polyphenols, were widely employed and released as pollutants in a variety of industries, including textiles, food, and cosmetics. Biological oxidation process that used oxidizing enzymes to breakdown pollutant compounds were environmentally favorable. However, due to the cell toxicity of metal ions supplements used for the biosynthesis of oxidizing enzymes like laccase, their efficient application for biological degradation is limited. In this study, we aimed to boost laccase activity by introducing high copper resistance into whole-cell biocatalysts through irradiation-based accelerated evolution. Bacillus velezensis MBLB0692, a laccase producing bacterium, was employed as model strain that exhibited severe sensitivity under 10 mM copper. The selected Cu- resistant mutants not only overcame growth inhibition, but also increased laccase activity by 2.6-fold. The qRTPCR analysis confirmed that mutants showed significant change in gene expressions related to laccase generation and copper-related functions. Furthermore, dye decolorization assays showed that mutants degrade synthetic dyes more efficiently under high copper conditions. The varying decolorization efficiencies across dyes were attributed to differences in dye structure and the potential influence of copper on enzyme activity. Collectively, these findings emphasize the interaction between copper concentration and laccase activity, and present implications for environmental bioremediation.